Parameter “Hidup yang Baik”: Tegangan antara HAM, Agama, dan Sains - Sugiharto, I. Bambang (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2018)
In terms of the parameter of ‘Good Life’, the Declaration of Human Rights as well as the ideals of religions and science have in fact been criticized respectively, and considered flawed. While the Declaration of Human Rights is universal in character – hence they can become a point of convergence among different religions – it is also susceptible to political manipulation, and subject to criticism from particular religious perspectives as well as from scientific outlook. As with science itself, its perspective is considered too narrow and mundane, when viewed from religious perspectives, that is, science deliberately leaves out the mysterious transcendental dimension inherent in human life. On the other hand, religion has also been under severe criticisms these days, due to its contradictory tendencies. At this juncture, atheist scientists come up with a point of view which they claim to be more neutral and objective as far as it concerns the ideal of ‘good life’. At least this is what Sam Harris believes it to be, in his idea of “moral landscape”.